2001
DOI: 10.1212/wnl.56.12.1672
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal SAH

Abstract: Endovascular treatment may cause less structural brain damage than surgery and have a more favorable cognitive outcome. However, cognitive outcome appears to be dictated primarily by the complications of SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
4
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 18 publications
(12 reference statements)
7
88
4
6
Order By: Relevance
“…[27][28][29][30][31] Many of these studies used single-slice CT at 1 year, which would probably miss small DCI. They used many specific neuropsychological tests, such as copy and delayed production of Rey figure and modified Stroop test, for assessments.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31] Many of these studies used single-slice CT at 1 year, which would probably miss small DCI. They used many specific neuropsychological tests, such as copy and delayed production of Rey figure and modified Stroop test, for assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Other small nonrandomized studies have also found less cognitive impairment with endovascular treatment. 24 However, both studies had limitations; the former was conducted on a relatively small sample and the latter on a nonrandomized group. We have shown in N-ISAT that cognitive impairment was common in patients who were not otherwise disabled according to the mRS and that cognitive impairment was more frequent in the neurosurgery group.…”
Section: Discussionmentioning
confidence: 99%
“…16,27,28,45,77,94 A few studies, however, indicate that clipped patients are more depressed and perform poorer on tests of executive function, visual memory, and verbal memory relative to their coiled counterparts. 16,45,95,96 Why clipping is associated with greater cognitive impairment in these studies is unclear.…”
Section: Al-khindi Et Al Outcome After Aneurysmal Subarachnoid Hemorrmentioning
confidence: 91%
“…Another possibility is that clipped patients may have more brain injury; Hadjivassiliou and colleagues 95 found that 48% of clipped patients had focal encephalomalacia compared with 0% of coiled patients. Moreover, a significantly greater proportion of clipped patients had infarcts (87%) relative to coiled patients (57%).…”
Section: Al-khindi Et Al Outcome After Aneurysmal Subarachnoid Hemorrmentioning
confidence: 99%
See 1 more Smart Citation